G-andC-banding in Magnaporthe grisea chromosomes - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Chromosome of Magnaporthe grisea were observed using G- and C-banding methods. The use of G-banding chromosome of M. grisea revealed that the typical G-band at promethaphase to early niethaphase stage could be observed. The G-banding method of M. grisea developed here can be applied and practically used in other fungi. In this study the C-band of M. grisea could not be observed by Cbanding method.